2022
DOI: 10.1097/lgt.0000000000000644
|View full text |Cite
|
Sign up to set email alerts
|

The Vaginal Microbiome: II. Vaginal Dysbiotic Conditions

Abstract: This series of articles, titled The Vaginal Microbiome (VMB), written on behalf of the International Society for the Study of Vulvovaginal Disease, aims to summarize the recent findings and understanding of the vaginal bacterial microbiota, mainly regarding areas relevant to clinicians specializing in vulvovaginal disorders.Materials and Methods: A search of PubMed database was performed, using the search terms "vaginal microbiome" with "dysbiosis," "bacterial vaginosis," "cytolytic vaginosis," "desquamative i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 71 publications
(164 reference statements)
0
28
0
2
Order By: Relevance
“…However, an excessive number of lactobacilli is associated with cytolytic vaginosis, and the state of various microbes during BV progression affects the clinical presentation and pathogenesis of the disease. Furthermore, the heterogeneity and diversity within the genus Gardnerella may impact BV progression [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, an excessive number of lactobacilli is associated with cytolytic vaginosis, and the state of various microbes during BV progression affects the clinical presentation and pathogenesis of the disease. Furthermore, the heterogeneity and diversity within the genus Gardnerella may impact BV progression [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…BV differs from the rest of vaginal infections because usually, inflammation is not present. It is characterized by a shift in vaginal microflora with a significant decrease or even disappearance of lactobacilli and an increase in G. vaginalis , Atopobium vaginae , different anaerobic bacteria and a plethora of other microorganisms that cannot be cultured, and, as a result, their identification can be achieved only by molecular methods [ 29 , 30 ]. Furthermore, it has been demonstrated that BV is not only a polymicrobial infection but in fact a more complex clinical entity since it is characterized by biofilm formation [ 30 , 31 ], which could offer a possible explanation for the frequent recurrences observed [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized by a shift in vaginal microflora with a significant decrease or even disappearance of lactobacilli and an increase in G. vaginalis , Atopobium vaginae , different anaerobic bacteria and a plethora of other microorganisms that cannot be cultured, and, as a result, their identification can be achieved only by molecular methods [ 29 , 30 ]. Furthermore, it has been demonstrated that BV is not only a polymicrobial infection but in fact a more complex clinical entity since it is characterized by biofilm formation [ 30 , 31 ], which could offer a possible explanation for the frequent recurrences observed [ 15 ]. The increased prevalence of the microorganisms associated with BV in both our groups, although significantly increased in the pubertal group, is a matter of concern for future implications in their reproductive potential since BV has been associated with pelvic inflammatory disease (PID) and thus, with subfertility [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacilli protect women from pathogenic microbes. The development of imbalanced microbiota composition leads to a pathological condition called dysbiosis, a state which has been linked to various disorders and diseases typical for the urogenital tract [6][7][8][9][10]. For example, anaerobic bacteria such as Gardnerella, Atopobium, and Prevotella spp.…”
Section: Introductionmentioning
confidence: 99%